Combustion aerosols from mineral oil industrial fires: Physicochemical characterization and toxicity in bronchial epithelial cells at the air-liquid interface - C. Méausoone; T. Rogez-Florent; C. Castilla; L. Chevalier; C. Bouzar; P. Cardinael; T. Legeard; S. Tisse; J. Yon; F. Portet-Koltalo; E. Varea; B. Patte-Rouland; et al. (Environmental Pollution, 2026)

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Spondias tuberosa Arruda (Anacardiaceae) ethanolic leaf extract as a source of natural products inhibiting quorum sensing and pyocyanin production in planktonic Pseudomonas aeruginosa - A.S. Tareau; P.E. Bodet; J.R. Guedes da Silva Almeida; M. Barreau; O. Lesouhaitier; A. Tahrioui; R. Gonçalves de Oliveira Junior; R. Grougnet; P. Sitarek; L. Quintans-Junior; K. Baranger; S. Chevalier; et al. (Phytochemistry Letters, 2025)

No deformation propagation outward of the plateau across the Yalong Thrust Belt in Southeast Tibet - P. Pitard; A. Replumaz; P.H. Leloup; M.-L. Chevalier; S. Wang; M. Bai; X. Ou; M. Bernet; M. Balvay; E.R. Sobel; A. Vezinet; C. Gautheron; et al. (Tectonophysics, 2025)

Functional and nutritional properties of fava bean ingredients processed by extrusion - I. Jebalia; G. Della Valle; D. Dupont; V. Santé-Lhoutellier; H. Rabesona; G. Henry; S. Chevalier; M. Guillevic; A. Germain; G. Chesneau; M. Kristiawan (Food Research International, 2025)

P24-08 Chronic exposure to low-doses of maneb and manganese alters differentiation and lipid accumulation in hepatocytes in vitro - L. Chevalier; S. Pierre; M. Dufresne; M. Marceau; C. Pinteur; A. Corlu; B. Le Magueresse-Battistoni; P. Loyer (Toxicology Letters, 2025)

Therapeutic Drug Monitoring of Biologics: Current Practice, Challenges and Opportunities – a Workshop Report - Sophie Shubow; Michele Gunsior; Amy Rosenberg; Yow-Ming Wang; Tara Altepeter; Daphne Guinn; Mohsen Rajabiabhari; Joseph Kotarek; Diane R. Mould; Honghui Zhou; Adam S. Cheifetz; Sandra Garces; et al. (The AAPS Journal, 2025)

Long-term impact of embryonic exposure to ethinylestradiol and clotrimazole on behavior and neuroplasticity in zebrafish (Danio rerio) - M. Blanc-Legendre; L. Guillot; L. Chevalier; C. Malleret; K. Le Menach; P. Pardon; H. Budzinski; F. Brion; S. Sire; P. Coumailleau; T.D. Charlier; E. Pellegrini; et al. (Environmental Toxicology and Pharmacology, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

P21-62 The copper-based nanopesticide Kocide 3000® worsens development of colitis in mice as a function of sex, and disrupts the intestinal barrier function in an enteroid-derived epithelial cell monolayer model from mouse gut organoids - E. Casale; Y. Malaisé; C. Cartier; E. Gaultier; L. Chevalier; T. You; S. Dupont; E. Houdeau; B. Lamas (Toxicology Letters, 2024)

Influence of the Rhone River intrusion on microplastic distribution in the Bay of Marseille - A. Alcaïno; L. Vidal; L. Licari; C. Paillès; S. Conrod; J. Dauvier; C. Chevalier; C. Pinazo; M. Grelaud; P. Ziveri (Regional Studies in Marine Science, 2024)

Aging is associated with impaired triggering of TRPV3-mediated cutaneous vasodilation: a crucial process for local heat exposure - Lisa S. Martin; Audrey Josset-Lamaugarny; Thomas El Jammal; Sylvie Ducreux; Fabien P. Chevalier; Bérengère Fromy (GeroScience, 2023)

A population of mitochondrion-rich cells in the pars recta of mouse kidney - M. S. Forbes; B. A. Thornhill; C. I. Galarreta; R. L. Chevalier (Cell and Tissue Research, 2016)

Hydrological variability of major French rivers over recent decades, assessed from gauging station and GRACE observations - L. Chevalier; B. Laignel; N. Massei; S. Munier; M. Becker; I. Turki; A. Coynel; A. Cazenave (Hydrological Sciences Journal, 2014)

Expression and characterization of plasma membrane aquaporins in stomatal complexes of Zea mays - Robert B. Heinen; Gerd Patrick Bienert; David Cohen; Adrien S. Chevalier; Norbert Uehlein; Charles Hachez; Ralf Kaldenhoff; Didier Le Thiec; François Chaumont (Plant Molecular Biology, 2014)

Eutrophication as a driver of r ‐selection traits in a freshwater fish - M. Lin; M. Chevalier; S. Lek; L. Zhang; R. E. Gozlan; J. Liu; T. Zhang; S. Ye; W. Li; Z. Li (Journal of Fish Biology, 2014)
This study tested whether eutrophication could influence life‐history traits of a cyprinid, Chanodichthys erythropterus , in 10 Chinese lakes. Using the von Bertalanffy growth model, the asymptotic length ( L ∞ ) and the growth performance index ( I GRO ) were significantly affected by eutrophication. The gonado‐somatic index ( I G ) and relative fecundity ( F R ) were significantly lower in mesotrophic lakes than in eutrophic and hypertrophic lakes. These results indicate that increasing eutrophication affects the life‐history tactics of a freshwater fish.

Lipid biomarkers for anaerobic oxidation of methane and sulphate reduction in cold seep sediments of Nyegga pockmarks (Norwegian margin): discrepancies in contents and carbon isotope signatures - Nicolas Chevalier; Ioanna Bouloubassi; Alina Stadnitskaia; Marie-Hélène Taphanel; Jaap S. Sinninghe Damsté (Geo-Marine Letters, 2014)

Characterization of five RALF-like genes from Solanum chacoense provides support for a developmental role in plants - Hugo Germain; ric Chevalier; Sbastien Caron; Daniel P. Matton (Planta, 2005)

Effects of Dietary Restriction and Metal Supplementation on the Accumulation of Iron-Laden Glial Inclusions in the Aging Rat Hippocampus - O. Borten; A. Liberman; B. Tuchweber; S. Chevalier; G. Ferland; H.M. Schipper (Biogerontology, 2004)

Intracellular vesicular trafficking in the gill epithelium of urea-excreting fish - P. Laurent; C. M. Wood; Y. Wang; S. F. Perry; K. M. Gilmour; P. Part; C. Chevalier; M. West; P. J. Walsh (Cell and Tissue Research, 2001)

The physiological life cycle of wheat: Its use in breeding and crop management - B. Klepper; R.W. Rickman; S. Waldman; P. Chevalier (Euphytica, 1998)